2003
DOI: 10.1002/jbt.10072
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral administration of arabic gum on cisplatin‐induced nephrotoxicity in rats

Abstract: It has been recently postulated from our laboratory that Arabic gum (AG) offers a protective effect in the kidney of rats against nephrotoxicity induced by gentamicin via inhibiting lipid peroxidation. It has also recently shown a powerful antioxidant effect through scavenging superoxide anions. In this study we utilized a rat model of cisplatin (CP)-induced nephrotoxicity to determine its peak time following (1, 2, 5, and 7 days) of a single CP (7.5 mg/kg, i.p.) injection. Also, a possible protective effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
43
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 38 publications
11
43
0
Order By: Relevance
“…These data are in good agreement with previous studies. 4,[12][13][14][21][22][23] Although the mechanism of CDDP-induced nephrotoxicity is exactly unknown, several studies have suggested that the nephrotoxicity is induced by lipid peroxidation and free radicals. On the other hand, many antioxidants have been shown to be protective against CDDP-induced nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data are in good agreement with previous studies. 4,[12][13][14][21][22][23] Although the mechanism of CDDP-induced nephrotoxicity is exactly unknown, several studies have suggested that the nephrotoxicity is induced by lipid peroxidation and free radicals. On the other hand, many antioxidants have been shown to be protective against CDDP-induced nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, many antioxidants have been shown to be protective against CDDP-induced nephrotoxicity. [12][13][14] Also, various free radical scavengers have been shown to be effective in protection against CDDP-induced nephrotoxicity, and treatment with such agents provides significant protection against CDDP-induced acute renal failure. 4,24) Cap and its analogues have more effective antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A huge body of experimental evidence has suggested that reactive oxygen species (ROS) are involved in the pathogenesis of gentamicin nephrotoxicity. 5,9) In this regard, gentamicin was found to enhance the production of hydrogen peroxide by rat renal cortical mitochondria in vitro.…”
Section: Discussionmentioning
confidence: 98%
“…Common antioxidant N-acetylcysteine, Vitamin E, Carvedilol protects against cisplatin induced renal damage (Abdelrahman et al, 2010;Appenroth et al, 1997;Carvalho Rodrigues et al, 2012;Carvalho Rodrigues et al, 2013;Nematbakhsh and Nasri, 2013;Riga et al, 2013). Broccoli derived sulforaphane, fruit derived fisetin, asian spice derived curcumin, capsaicin and arabic gum prevents cisplatin induced nephropathy (Al-Majed et al, 2003;Gaona-Gaona et al, 2011;Guerrero-Beltran et al, 2010Jung et al, 2014;Kursunluoglu et al, 2014;Sahu et al, 2014;Trujillo et al, 2013). Transcriptional regulator NRF2 and its target heme oxygenase-1 have critical role in cisplatin mediated renal damage (Aleksunes et al, 2010;Sahin et al, 2010aSahin et al, , 2010bShiraishi et al, 2000).…”
Section: Introductionmentioning
confidence: 98%